The quest for multi-functional medicines: path for progress: the tamoxifen story - Jordan, V. Craig (Henry Stewart Talks, 2011)
Tamoxifen is a pioneering medicine that was re-invented from it's original use because it failed as a contraceptive. Tamoxifen prevents the growth and development of breast cancer and is a pioneering medicine used to treat breast cancer. It is estimated that millions of women are alive today because of tamoxifen treatment. It is also the first medicine approved by the Food & Drug Administration for the prevention of any cancer.
Reviewed at 2018/01/17